2003
DOI: 10.1124/jpet.102.042960
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the α1 or β2 Subunit of GABAAReceptors Reduces Actions of Alcohol and Other Drugs

Abstract: Enhancement of the activation of GABA A receptors is a common feature of many sedative and hypnotic drugs, and it is probable that the GABA A receptor complex is a molecular target for these drugs in the mammalian central nervous system. We set out to elucidate the role of the two predominant (␣ 1 and ␤ 2 ) subunits of GABA A receptor in sedative drug action by studying mice lacking these two subunits. Both ␣ 1 (Ϫ/Ϫ) and ␤ 2 (Ϫ/Ϫ) null mutant mice showed markedly decreased sleep time induced by nonselective be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
5
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 32 publications
(38 reference statements)
10
60
5
2
Order By: Relevance
“…While the finding of gender difference in this study is not clear, it should be noted here that this is not uncommon in animals (eg, Blednov et al 36 ) and human studies (eg, Bell et al 44 ). Nevertheless, this should be interpreted with caution as such difference may be caused by biased sampling or simply, a matter of chance.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…While the finding of gender difference in this study is not clear, it should be noted here that this is not uncommon in animals (eg, Blednov et al 36 ) and human studies (eg, Bell et al 44 ). Nevertheless, this should be interpreted with caution as such difference may be caused by biased sampling or simply, a matter of chance.…”
Section: Discussionmentioning
confidence: 49%
“…An observation worth mentioning here is that, while there was no difference of pentobarbital action between wild types and the b2À/À and a1À/À mice, the duration of loss of righting reflex produced by ethanol was decreased in male mice for both null types; no differences were observed in ethanol-induced sleep in female mice. 36 These suggest that some genetic effects of the GABA subunit genes can be gender specific. Unfortunately, none of these animal studies examined substance addiction behavior directly.…”
Section: Discussionmentioning
confidence: 99%
“…The results from our sleep time study, together with the results from the motor activity analysis, lend credence the notion that a decrease in β2 protein expression translates to a functional loss of the GABA A receptor activity. Blednov et al (2003) showed a significant decrease in etomidateinduced sleep times in β2 knockout mice when compared to wild-type mice, although another study did not observe this effect (O'Meara et al, 2004). The reasons for the discrepancy between the studies are unclear but might be related to differences in the doses and route of administration and dose (40 mg/kg intraperitoneal vs. 5-5 mg/kg intravenous).…”
Section: Behavioural Phenotype Of Fmr1 Knockout Micementioning
confidence: 96%
“…deletions of particular GABA A receptor subunits (Blednov et al, 2003;Kralic et al, 2003). To address this possibility and confirm that DKO mice did not show increased sleep time after activation of GABA A receptors, we measured sleep time after administration of THIP, a direct agonist of the GABA A receptor.…”
Section: Adenylyl Cyclase Knock-out Mice Do Not Demonstrate Enhanced mentioning
confidence: 99%